Magic Formula: Sebuah Tinjauan dalam Prediksi Perusahaan-Perusahaan Unggulan di Indonesia - Ni Luh Putu Uttari Premananda; Md. Yudyantara Risadi (Penerbit Goodwood, 2023)
Purpose: This study aimed at investigating the performance of a value investing strategy called the “Magic Formula”, introduced by Joel Greenblatt (2006), applied to the Indonesian Stock Exchange. Magic Formula is a simple stock selection strategy by ranking stocks based on calculating Return on Capital and Earnings Yield. Methodology: First, this study examined stocks listed on the Indonesia Stock Exchange represented by the Kompas 100 index measuring the price performance of 100 stocks that have good liquidity and large market capitalization. This step was followed by eliminating finance stocks because they have different debt postures which will affect the calculation in the next stage. The next step was to choose the top thirty stocks from the combined rank to become a portfolio. Portfolio rebalancing is conducted annually. Sharpe, Treynor, and Jensen’s Alpha analysis were used to measure returns adjusted for risk. Results: This study showed that using return on capital and earnings yields can produce higher average returns than the market index from April 2015 to April 2019. The Magic Formula portfolio yields an average return of 12.76% and the market produces average returns of 6.89% during the period under test. Limitations: The obtained data were derived from 5 years-data of the Indonesia Stock Market. in order to neglect the Efficient Market Hypothesis, the collection of wider data was required. besides, the result of this study is unusable to test the Efficient Market Hypothesis at weak or strong level. Contribution: This study contributes empirical evidence that the Magic Formula is a solid investment model especially considering its simplicity. Magic Formula can be used as an early stage in the process of selecting a company to invest in.